Bonsu: the interactive phase retrieval suite - Newton, Marcus C.; Nishino, Yoshinori; Robinson, Ian K. (Journal of Applied Crystallography, 2012)
Coherent X‐ray diffraction imaging has received considerable attention as a nondestructive method for probing material structure at the nanoscale. However, tools for reconstructing and analysing data in both two and three dimensions have lagged somewhat behind. Bonsu, the interactive phase retrieval suite, is the first software package that allows real‐time visualization of the reconstruction of phase information in both two and three dimensions. It comes complete with an inventory of algorithms and routines for data manipulation and reconstruction. Bonsu is open source, is designed around the Python language (with C++ bindings) and is largely platform independent. Bonsu is made available under version three of the GNU General Public License and can be found at http://www.code.google.com/p/bonsu.